TEACHER PROFESSIONALITY STRATEGY USING APPLICATION OF WHATSAPP (WA) IN PANDEMIC COVID-19 IN MTS PRIVATE DARUL ARAFAH LAU BAKERI KUTALIMBARU DELI SERDANG - Rahmat Hidayat; Handoko Handoko; M. Rizki; Ulfi Sayyidatul Fitria; Novia Elisha (Jurnal Sabilarrasyad, 2020)
At this time one of the instantaneous programs inclusive of WhatsApp or WA has been so effortlessly implemented and preferred by numerous layers of age. Most of the users of this software are young adults of faculty age from early adolescence to students. The COVID-19 pandemic has changed numerous elements of human life today, especially inside the area of education. This calls for all elements of schooling to conform and maintain the rest of the semester. The reason of this have a look at is an overview of mastering in the course of the COVID-19 pandemic. They have an impact on of WhatsApp is very sturdy on the getting to know machine in School. Generally WA users point out the cause about selecting this utility is because of the availability of numerous conveniences that are further to no longer voicing alias free. This studies makes use of descriptive analysis research method. Online gaining knowledge of is an effective answer for activating classrooms even though colleges have closed. This gaining knowledge of approach with WhatsApp media is essential for instructor professionalism in step with the continuity of coaching and mastering activities inside the contemporary COVID-19 pandemic conditions